Spectrophotometric Determination of Phosphate in Sugarcane Juice, Fertilizer, Detergent and Water Samples by Molybdenum Blue Method - Pradhan, Samjhana; Pokhrel, Megh Raj (Scientific World, 2013)
A simple and sensitive spectrophotometric method has been developed for the determination of phosphate in mg per liter (parts per million) concentration range in sugarcane juice, water, fertilizer and detergent samples. The amount of phosphate is determined by molybdenum blue phosphorus method in conjugation with UV-visible spectrophotometer. This method is based on the formation of phosphomolybdate complex with the added molybdate followed by the reduction of the complex with hydrazine hydrate in aqueous sulphuric acid medium. The system obeys Lambert-Beer’s law at 840 nm in the concentration range 0.1-11 ppm. The colour intensity of the reduced phosphomolybdate solution is found to be proportional to the amount of phosphate present in sugarcane juice, water, fertilizer and detergent samples. The reaction conditions as well as the various experimental parameters affecting the development and stability of the coloured complex were carefully investigated and optimized for the quantitative determination of phosphate present in various samples. The optimized concentrations of various reagents used are 0.20N sulphuric acid, 0.02M hydrazine hydrate and 0.20% ammonium molybdate. The effect of time on the formation of phosphomolybdenum blue complex and addition of the order of the reagents was also studied. Scientific World, Vol. 11, No. 11, July 2013, page 58-62 DOI: http://dx.doi.org/10.3126/sw.v11i11.9139